2018
DOI: 10.31220/osf.io/9374a
|View full text |Cite
|
Sign up to set email alerts
|

Understanding coffee farmers: using games to explore future coffee agroforestry landscapes in the Western Ghats (India).

Abstract: Deforestation and biodiversity loss in agroecosystems are generally the result of rational choices, not of a lack of awareness or knowledge. Despite both scientific evidence and traditional knowledge that supports the value of diverse production systems for ecosystem services and resilience, a trend of agroecosystem intensification is apparent across tropical regions. These transitions happen in spite of policies that prohibit such transformations. We present a participatory modelling study run (1) to understa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Farmers in our research used the game as support for learning, sharing knowledge and practices towards opportunities and against the obstacles. The support of serious games as forecasting scenario evaluation tool for agricultural land use planning has been presented in numerous research studies with similar results to ours: educational purpose, knowledge and management practices sharing, conflict mediation and leadership assessment (Garcia et al 2018;Speelman et al 2019).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Farmers in our research used the game as support for learning, sharing knowledge and practices towards opportunities and against the obstacles. The support of serious games as forecasting scenario evaluation tool for agricultural land use planning has been presented in numerous research studies with similar results to ours: educational purpose, knowledge and management practices sharing, conflict mediation and leadership assessment (Garcia et al 2018;Speelman et al 2019).…”
Section: Discussionsupporting
confidence: 74%
“…Rethinking and developing management strategies agroecosystems towards more sustainable agroforested landscapes have been addressed through serious games (García- Barrios et al 2008;Garcia et al, 2018) and action research based on local knowledge and beliefs (Bergez et al 2014;Kishita et al 2016). Action research allows to study and rethink the farming system as a biophysical, economic and social subject shaping scientific and local knowledge and practices (Warner 2007;Hoolohan et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the development of a theory of change for how different interventions can be used to address illegal wildlife trade allows practitioners to identify which types of interventions are most likely to be appropriate in a given context (Biggs et al 2016). In another example, in the Western Ghats of India, interventions involving the restitution of tree rights to local coffee growers, which were proposed to promote the intercropping of native tree species with coffee plantations, were empirically tested using a role-playing game modelling approach (Garcia 2013). The findings revealed that, contrary to their original aim, the proposed interventions risked speeding up the transition to a landscape dominated by the exotic silver oak Grevillea robusta rather than promoting native species.…”
Section: Intervention Framingmentioning
confidence: 99%
“…The foundation of companion modelling is the willingness to incorporate on equal footing the multiple and often conflicting viewpoints of the stakeholders into a single model, validated by all stakeholders involved in the process [33][34][35]. Through workshops facilitated by the research team, stakeholders collectively decide and organise the knowledge they consider relevant for the problem at stake (e.g., [36][37]).…”
Section: Participatory Approachmentioning
confidence: 99%